RANCANG BANGUN SISTEM INFORMASI PEMINJAMANSARANA DAN PRASARANA BERBASIS WEB : Studi Kasus Universitas Pembangunan Nasional Veteran Jakarta - Hanif Rifky Witjaksono (2020)
The propose process for reservation facilities and infrastructure in Universitas Pembangunan Nasional Veteran Jakarta is still done in a conventional way. An applicant who want to reserve must come to Biro Umum dan Keuangan division by bringing a letter of application to be submitted. An applicant can wait within a span of one or several days to get a response letter in Biro Umum dan Keuangan or UHT division. on the other hand, an applicant can experience difficulties in the reservation propose process due to the list schedule can only be seen in Biro Umum dan Keuangan room, the officers related to facilities and infrastructure that are not necessarily present. The facility and infrastructure reservation information system is one of the systems that can be applied in the Universitas Pembangunan Nasional Veteran Jakarta environment. This system is designed to improve the conventional system so that it can make it easier for borrowers to apply for reservation, receive information, and can also facilitate the management of facilities and infrastructure for the data collection process. Systems design analysis method uses UML (Unified Modeling Language) modeling method. This system development method uses the RAD (Rapid Application Development) model.